2021
DOI: 10.3390/diagnostics11020189
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Texture Analysis Using 11C-Methionine Positron Emission Tomography Predicts Survival after Surgery for Glioma

Abstract: Background: Positron emission tomography with 11C-methionine (MET) is well established in the diagnostic work-up of malignant brain tumors. Texture analysis is a novel technique for extracting information regarding relationships among surrounding voxels, in order to quantify their inhomogeneity. This study evaluated whether the texture analysis of MET uptake has prognostic value for patients with glioma. Methods: We retrospectively analyzed adults with glioma who had undergone preoperative metabolic imaging at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A total of 23 of the 220 studies focused on oligodendrogliomas, gliomas, and glioblastomas [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] employing several PET tracers: 11C-Metionine (n = 7), 18F-FET (n = 7), 18F-FDG (n = 4), 18F-FDOPA (n = 3), 18F-FLT (n = 1), 18F-FMISO (n = 1). These studies included an average of 78.4 patients (range: 32–160), 6/23 (26.1%) including more than 100 patients, 3/23 (13.0%) with prospective data and 8/23 (34.8%) with validation sets.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 23 of the 220 studies focused on oligodendrogliomas, gliomas, and glioblastomas [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] employing several PET tracers: 11C-Metionine (n = 7), 18F-FET (n = 7), 18F-FDG (n = 4), 18F-FDOPA (n = 3), 18F-FLT (n = 1), 18F-FMISO (n = 1). These studies included an average of 78.4 patients (range: 32–160), 6/23 (26.1%) including more than 100 patients, 3/23 (13.0%) with prospective data and 8/23 (34.8%) with validation sets.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al 58 , Kickingereder et al, 59 and Chaddad et al 60 showed that a prognostic model built with second order texture features extracted from pre-treatment mpMRI are significantly associated to OS in GBM (C-index 0.70 58 , C-index 0.65 59 , log-rank test p -value < 0.01 60 ). Carles et al 33 and Manabe et al 61 observed that second-order texture features extracted from [18F]-FDG PET and MET-PET can predict OS (p 0.038 33 and p < 0.05 61 , respectively). Verma et al 62 found higher order pre-treatment MRI features as a prognostic marker for PFS in GBM (C-index 0.80).…”
Section: Discussionmentioning
confidence: 99%
“…In our review of relevant studies, as summarized in Table S13 , numerous pre-treatment MRI-based radiomics investigations focus on the patient prognosis in GBM 58 60 , 62 , 64 67 . However, only a limited number of studies incorporate pre-treatment MET-PET with small sample sizes (N = 42 61 , N = 52 63 ). Considering the significance of residual tumour burden as a prognostic imaging biomarker in GBM 18 , 19 , understanding the residual tumour status post-surgery may aid in refining treatment planning and tailoring therapies to the specific tumour burden, potentially improving treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%